Propuesta de plan de importación y comercialización de césped sintético con fines decorativos y deportivos en la ciudad de Guayaquil, año 2013. - Ortiz Guevara, Dolores del Rocio (2015)
Guayaquil has no green areas, parks and houses are limited in green areas, resulting in a lack of adornment in the city, this project seeks to improve the city environment by encouraging the use of synthetic turf for ornamental use and athletic, as it requires no major maintenance, and high profitability is expected due to the high demand for this product.